Technical, Physical, and Academic Challenges in Online Learning: Evidence from Nursing Students in Foundations of Nursing Practice - Cyril B. Romero; Benilda M. Oliva; Marc Jhames Resoco Temeña; Julie S. Cervas (The Indonesian Institute of Science and Technology Research, 2026)
The rapid integration of digital technologies in higher education has transformed the teaching and learning process, particularly in nursing education where flexibility and accessibility are essential. This study examined the challenges of online learning and their repercussions on the academic performance and student engagement of BSN 1J students enrolled in NCM 103 (Foundations of Nursing Practice) at the University of Saint Anthony during the Second Semester of School Year 2025–2026. Specifically, the study investigated students’ demographic profile, challenges encountered in online learning, the relationship between demographic characteristics and online learning challenges, and the effects of these challenges on academic performance and engagement. A descriptive-correlational research design with an evaluative approach was employed. The respondents consisted of forty (40) nursing students selected through total enumeration sampling. Data were collected using a researcher-developed questionnaire administered through Google Forms. Frequency counts, percentages, weighted means, and the Chi-Square Test of Independence were utilized to analyze the data. The findings revealed that the respondents generally experienced challenges related to technical adaptability, internet access and equipment, physical health barriers, academic engagement, and attitudes toward online learning. Internet connectivity and access to learning devices emerged as the most significant challenges, while headaches, eye strain, and back fatigue were commonly reported physical health concerns. Students also experienced difficulties in time management, maintaining motivation, and sustaining active participation in online classes. These challenges negatively affected students’ concentration, learning efficiency, academic performance, and engagement. The study concludes that online learning presents multidimensional challenges that require comprehensive institutional support. Strengthening technological infrastructure, improving access to learning resources, providing technical assistance, and implementing student-centered support programs are recommended to enhance academic success and engagement among nursing students in online learning environments.